DIPLOMASI EKONOMI INDONESIA DENGAN UNI EROPA: STUDI ANALISIS OPERATION RESEARCH MENGGUNAKAN METODE GAME THEORY - Gth Hasto Respatyo; Indra Kristian (Jurnal Dinamika Global, 2025)
This literature describes the economic diplomacy of Indonesia - the European Union in an effort to optimize Indonesia's national interests in the economic sector. Using the quantitative approach of Games Theory according to Abraham Wald and L.J. Savage, Indonesia's economic diplomacy through CEPA in increasing the value of trade and investment. This study aims to determine the most optimal actions related to Indonesian Exports and Imports in determining the priority of commodities to be imported or exported, with the smallest risk.